Gestión administrativa en la calidad de los servicios de la Unidad Médica de la Empresa Municipal de Agua Potable y Alcantarillado de Riobamba durante el período 2018-2021. - Cabezas Quito, Lorena Paola (2025)
The aim of the present research work is about "ADMINISTRATIVE MANAGEMENT IN THE QUALITY OF SERVICES OF THE MEDICAL UNIT OF THE MUNICIPAL DRINKING WATER AND SEWER COMPANY OF RIOBAMBA (2018-2021)" These have been focused on determining how the administrative management affects the quality of the services of this medical unit. A mixed approach was used that combined quantitative and qualitative analyses, with a non experimental and cross-sectional design. Furthermore field and documentary research methods were used, with a descriptive level to obtain a deep understanding. Data collection was carried out through surveys using a questionnaire adapted to evaluate administrative management and the perception of quality of services by 160 users selected through statistical calculations. The results of the Pearson correlation analysis showed a positive and significant relationship between the administrative management and the service quality. The hypothesis of the study has supported, indicating that effective management has a considerable impact on the quality service of the Medical Unit. Specific strategies were recommended to improve the identified areas, in order to optimize the administrative processes and consequently offering a good service to the community. This study has provided a solid basis to implement corrective actions and continuous improvements in administrative management, directly benefiting health service users.